Pengaruh Lingkungan Kerja, Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Karyawan pada UD. EKA DWI TERPAL - Yosie Armando Setiawan; Hartono Hartono; Kasnowo Kasnowo (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
In today’s highly competitive era, companies strive to develop their businesses to stay ahead in the market. One of the most effective ways to achieve business development is by maximizing the management of available resources, with human resources (HR) playing a critical role in this process. Proper HR management can lead to optimal performance and enhance the company’s competitiveness. Several factors influence employee performance, including work environment, work discipline, and motivation. This study aims to examine the impact of work environment and work discipline on employee performance, with work motivation as a mediating variable at UD. EKA DWI TERPAL. The research was conducted by distributing questionnaires to all employees of UD. EKA DWI TERPAL, with a sample size of 48 employees using a saturated sampling technique. The data analysis technique used is Structural Equation Modeling Partial Least Squares (SEMP-PLS), supported by the SmartPLS software. The findings of the study are as follows: First, work environment has a direct positive and significant effect on motivation; second, work discipline has a direct positive and significant effect on motivation; third, work environment has a direct positive and significant effect on employee performance; fourth, work discipline has a direct positive and significant effect on employee performance; fifth, motivation has a direct positive and significant effect on employee performance; sixth, work environment has an indirect positive and significant effect on employee performance through motivation; and seventh, work discipline has an indirect positive and significant effect on employee performance through motivation. Overall, the study suggests that good management of work environment and work discipline can improve employee motivation and performance, enabling companies to achieve optimal performance.